Potent Cyclic Tetrapeptide for Lead Detoxification - Mohammed, Tagwa A; Meier, Christoph M; Kalvoda, Tadeáš; Kalt, Martina; Rulíšek, Lubomír; Shoshan, Michal S (Angewandte Chemie (International ed. in English), 2021)
Lead (Pb) is a ubiquitous poisonous metal, affecting the health of vast populations worldwide. Medications to treat Pb poisoning suffer from various limitations and are often toxic owing to insufficient metal selectivity. Here, we report a cyclic tetrapeptide that selectively binds Pb and eradicates its toxic effect on the cellular level, with superior potency than state-of-the-art drugs. The Pb-peptide complex is remarkably strong and was characterized experimentally and computationally. Accompanied by the lack of toxicity and enhanced stability of this peptide, these qualities indicate its merit as a potential remedy for Pb poisoning.
Keywords: Cell Survival; chelation therapy; lead poisoning; Humans; olovo; metal selectivity; Oligopeptides; buňky HT-29; Protein Binding; peptides; HT29 Cells; Lead; lidé; oligopeptidy; cyklické peptidy; Peptides, Cyclic; vazba proteinů; rational design; viabilita buněk